Program Pendidikan sebagai Upaya Pemenuhan Kebutuhan Peserta Didik Dalam Meningkatkan Prestasi Akademik - Setiawan, Heru; Hakim, Muhammad Nur; Tipa, Kurniayati (Islamic Education Management Study Program of STIT al Urwatul Wutsqo Jombang, East Java, Indonesia, 2025)
This study aims to examine the implementation of educational programs at SMA Negeri 2 Mojokerto and analyze its role in meeting the needs of students in order to improve academic achievement. The research method used is qualitative descriptive with a case study approach. Data were collected through observation, interviews, and documentation. The results of the study indicate that the preparation of educational programs at SMA Negeri 2 Mojokerto was carried out carefully and systematically at the beginning of the semester, taking into account the needs of students. Educational programs as an effort to meet the needs of students in improving academic achievement include tutoring activities, independent learning activities, project-based learning, and guidance and counseling. These programs are designed to provide comprehensive support so that students can achieve their academic potential optimally